Environmental Interpretation: How to Communicate Persuasively - Kara N. Youngentob; Mark E. Hostetler (EDIS)
This document will focus on how to target and communicate persuasively to your audience. The purpose of this document is to show you how to influence people's attitudes and behaviors. This document will not teach you how or when to use different modes of interpretation. Kiosks, brochures, and public talks are examples of interpretive modes. However, the information that you learn here can be combined with whatever mode(s) you choose. This document is WEC 169, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Services, Institute of Food and Agricultural Sciences, University of Florida. First published in November 2003.